2018
DOI: 10.1111/his.13505
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutation is predictive of outcome in patients with pulmonary sarcomatoid carcinoma

Abstract: Potentially targetable mutations can be identified in a subset of PSC, although most tumours harbour currently untargetable prognostically adverse TP53 and KRAS mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 39 publications
1
33
4
Order By: Relevance
“…84 Similarly, Mehrad and colleagues reported a significant correlation of KRAS mutations with worse patients' outcome. 86 We also showed that the presence of KRAS mutations significantly correlates with increased PD-L1 expression suggesting a possible correlation, to be further investigated, between these mutations and response to immunotherapy. 99 These results together with the recent emerging MEK inhibitors may imply a potential value of KRAS mutations as relevant predictive markers in orienting PSC tailored treatment.…”
Section: Clinical Impact Of Psc Molecular Profilingmentioning
confidence: 56%
See 1 more Smart Citation
“…84 Similarly, Mehrad and colleagues reported a significant correlation of KRAS mutations with worse patients' outcome. 86 We also showed that the presence of KRAS mutations significantly correlates with increased PD-L1 expression suggesting a possible correlation, to be further investigated, between these mutations and response to immunotherapy. 99 These results together with the recent emerging MEK inhibitors may imply a potential value of KRAS mutations as relevant predictive markers in orienting PSC tailored treatment.…”
Section: Clinical Impact Of Psc Molecular Profilingmentioning
confidence: 56%
“…The first clues about the genetic landscape of PSC became available only in the most recent years. [81][82][83][84][85][86] The raise and rapid expansion of the new sequencing techniques, together with the collection of relatively large series of PSC samples available for the analysis have represented major turning points in getting clues into the genetic assets of these tumors.…”
Section: Recent Insights Into Psc Genetic and Transcriptional Featuresmentioning
confidence: 99%
“…Copy number analyses have demonstrated loss of RB1, ATM and gains in EGFR. However, most PSCs have un‐targetable TP53 and KRAS mutations . Of note, MET exon 14 skipping has been reported to be associated with PSCs.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In addition, KRAS (30-40% of patients) and MET genes (13-20%) are the most common driver oncogene mutations noted in PSC (7). However, targetable mutations in PSC are less frequent than in NSCLC with adenocarcinoma histology, with EGFR mutations reported in 8-22% cases in various studies (7,(9)(10)(11). The efficacy of EGFR tyrosine kinase inhibitors (TKI) in PSC has also varied between studies, and was inferior when compared to adenocarcinoma (7).…”
Section: Discussionmentioning
confidence: 99%